Cover Image, Volume 57, Issue 11‐12. Issue 11 (2nd December 2019) - Terada, Maiko; Kawamata, Masaki; Kimura, Ryota; Sekiya, Sayaka; Nagamatsu, Go; Hayashi, Katsuhiko; Horisawa, Kenichi; Suzuki, Atsushi
Abstract : Cover illustration : The cover image is based on the Technology Report Generation of Nanog reporter mice that distinguish pluripotent stem cells from unipotent primordial germ cells by Atsushi Suzuki et al., https://doi.org/10.1002/dvg.23334 .